Recent Improvements to the Government Finance Statistics Yearbook Database in Response to Analytical Needs - Seiferling, Mike (IMF Working Papers; Working Paper ;, 2013)
The demand for high quality detailed public finance statistics covering a globally representative sample of countries has increased dramatically during the recent financial crisis. Due to the complexity of public finance statistics, however, such data tend to be either available in oversimplified high level aggregates and lacking in methodological transparency, or, available with a great level of detail and a unified methodological approach yet overly complicated to understand. The IMF's Government Finance Statistics Yearbook (GFSY) withdata over an almost 40 year period for almost 140 countries is a valuable database but with a complex structure requiring some specialty knowledge that most data users do not have. The IMF's Statistics Department embarked on several initiatives to improve its accessibility. The purpose of this paper is to provide a non-technical overview of the methodology and advantages of the GFSY database and discussion of how the database is improving to better meet the needs of the user community.